Fundamental concepts in computer science - Gelenbe, Erol, 1945-; Kahane, Jean-Pierre (Advances in computer science and engineering. Texts, 2009)
This book presents fundamental contributions to computer science as written and recounted by those who made the contributions themselves. As such, it is a highly original approach to a "living history" of the field of computer science. The scope of the book is broad in that it covers all aspects of computer science, going from the theory of computation, the theory of programming, and the theory of computer system performance, all the way to computer hardware and to major numerical applications of computers.